Service for Verification of Electronic Document’s Certificates - I. O. Tolokh; S. Yu. Mikhnevich; A. Yu. Siankevich (Цифровая трансформация)
The legislation of the Republic of Belarus currently establishes the same legal force for identical documents on paper and in electronic form, which have a mandatory requisite - an electronic digital signature. The article considers the system for managing public keys of electronic digital signature in the Republic of Belarus, as well as the concepts and definitions associated with this system. The technical normative legal acts in the field of cryptographic protection of electronic documents are analyzed. The necessity of verification of certificates of public keys of electronic digital signature is substantiated. Possible variants of the procedure for verifying public key certificates are described, their advantages and disadvantages are shown. An online service for checking public key certificates has been developed using open cryptographic libraries and public tools.